Ponte Jornalismo's coverage of Genivaldo Santos murder - Maia, Marta (2024)
In this study, we analyzed the journalistic coverage of the murder of Genivaldo de Jesus Santos in 2022, perpetrated by agents of the Federal Highway Police. We examined the configuration of Ponte Jornalismo's testimonial journalistic narratives, which mainly focus on covering state violence, racial, gender and human rights issues in Brazil. We also address the phenomenon of structural racism, and how Ponte covered the incident through a methodological protocol that addresses the individuation of the event, which highlighted the structural racism in force in the country.